ANALISIS KEPUTUSAN PEMBIAYAAN TALANGAN HAJI PADA NASABAH DI PT. BPRS METRO MADANI - Nur Fitriyaningsih; Jawoto Nusantoro; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This research is a qualitative research that aims to analyze the decision of financing hajj bailouts for customers. This research was conducted at PT BPRS Metro Madani, with data sources consisting of primary data sources. And the secondary data sources that the researchers used came from books, journals and theoretical articles, documents, and photos related to financial reports which discuss the Analysis of Decisions on the Financing of Hajj Bailout for Customers at PT. BPRS Metro Madani". Research Results The process of analyzing the feasibility of financing at BPRS Metro Madani using the analysis of: Character, capacity, capital, collateral, and Sharia compliance Hajj bailout product at PT. BPRS Metro Madani implements a multi-service Ijarah contract to take Ujrah as an advantage.